Optimisation of scintigraphic imaging of the novel therapeutic agent Ra-223 in the treatment of metastatic castration resistant prostate cancer. Issue 7 (July 2016) - Maguire, Susan; Gilligan, Paddy; Carson, Michael
Abstract : Introduction: Imaging of radionuclide therapy agents is useful in determining biodistribution, verification of correct pharmaceutical and to rule out extravasation in clinical administrations. The aim of this study was to optimise imaging of Ra-223 dichloride (Xofigo™) for patients with metastatic castration resistant prostate cancer. Materials and methods: A Jaszczak phantom and bar resolution phantom were used with 0.8 MBq of Ra-223 to evaluate image quality for a range of collimators, energy windows and matrices for planar and SPECT imaging (Siemens ECam, Erlangen). Clinical imaging was carried out twenty minutes post injection of Ra-223. Four sets of static images were obtained on two patients undergoing treatment, pre and post optimisation. Results: Optimum imaging parameters were found using planar imaging with a Xenon-133 energy window (80 kV photopeak, 20% energy window), 128 × 128 matrix. A medium energy collimator resulted in higher resolution images with reduced image noise compared to a low energy general purpose collimator. These parameters allowed for clinically acceptable image quality with an imaging time acceptable for patient comfort (20 min). Clinical imaging allowed visualisation of structures post administration of Ra-223. Post optimisation images were of better quality although pre and post optimisation images were clinically useful. Conclusion: Useful clinical information can be obtained from scintigraphic imaging of Ra-223. The quality of imaging improved with optimisation of imaging parameters.